Cross hedging in currency forward markets - Udo Broll (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1996)
In a framework for risk management a model of an international firm under exchange rate uncertainty is discussed. The firm can cross-hedge the exchange rate risk by using forwards of other country's currencies correlated to the spot exchange rate in question. The study investigates the implications of hedging exchange rate risk of less common currencies for an exporting firm.
Keywords: F21; F31; 330; exchange rate risk; currency forward markets; cross-hedge; Währungsmanagement; Hedging; Internationale Betriebswirtschaftslehre; Theorie